The Influence of Promotional Media and Brand Image on the Decision to Choose a High School with Digital Marketing as an Intervening Variable: Pengaruh Media Promosi dan Brand Image Terhadap Keputusan Memilih Sekolah Menengah Atas dengan Digital Marketing Sebagai Variabel Intervening - Fauzan, Risqi Rachmadi; Hermawan, Sigit; Supardi, Supardi; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2023)
This At the end of 2019 in December in Wuhan, China, the world was stirred up and people were made restless by the corona virus (Covid-19) which had an impact on all sectors of human life, not to mention the world of education. Media information promotion facilities used at SMA Hang Tuah 2 in carrying out the process of accepting new students (PPDB) in order to build a brand image by using the Digital Marketing system. The type of research that will be used is associative quantitative research, namely research that is asking for the relationship between two or more variables. This study aims to determine the influence of variables, namely the variable (X) promotional media and brand image on (Y) the decision to choose Hang Tuah 2 High School Sidoarjo. The data obtained were analyzed using SMART-PLS. Promotional media has no significant effect on election decisions. Brand Image has a significant influence on election decisions. Promotional media has no significant effect on digital marketing. Brand Image has a significant influence on digital marketing. Digital Marketing has a significant influence on election decisions. Promotional media does not have a significant influence on the selection decision through digital marketing as an intervening variable. Brand Image does not have a significant influence on election decisions through digital marketing as an intervening variable. Word of mouth is the most powerful promotional technique in this study, the role of people is very important in promoting services. Customers are very close to service delivery.